La Desigualdad En El Derecho De Vacaciones Para El Trabajador En General, En Relación Con Un Servidor Público - Rodríguez Chiriboga, Walter Fernando (2016)
The right to equal formal and material between all people, is one of the fundamental principles of our Constitution of the Republic, however, it is still seen inequality between workers and public servants in terms of economic benefits, vacation, among others. The subject of this research degree focuses on the holiday right worker to the public server, where a difference is established. The Labour Code provides that the worker is entitled to fifteen days of vacation for each year of service and from the fifth year will be entitled to one more day of vacation for every year of service without being able to exceed thirty. For its part, the Law on Public Service establishes thirty days of vacation for the public servant. If we analyze the legal provisions to which reference is made, you can clearly determine that there is a difference or unequal treatment between the public servant and worker and here is the main idea of my thesis work, and from my personal point of view I consider that there is a severe discrimination against workers because as a public servant, meet the same end maybe in different roles, but this does not entitle for one has fewer vacation days than the public servant, why which is essential to reform the Labor Code for an equal period of thirty days is set as holiday entitlement for the worker in general for each year of service